2020
DOI: 10.1002/ecy.3187
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Elton's diversity–invasibility hypothesis from belowground

Abstract: Sixty year ago, Charles Elton posed that species-rich communities should be more resistant to biological invasion. Still, little is known about which processes could drive the diversity-invasibility relationship. Here we examined whether soil-microbe-mediated apparent competition on alien invaders is more negative when the soil originates from multiple native species. We trained soils with five individually grown native species and used amplicon sequencing to analyze the resulting bacterial and fungal soil com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
32
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 62 publications
3
32
2
1
Order By: Relevance
“…It is well known that the species richness of native plant communities can affect the diversity, abundance activity of soil pathogens increase with species richness in native plant communities, then soils from native plant communities with higher species richness should have a stronger negative effect on the growth of invasive plants. For instance, in a recent study, Zhang et al (2020) showed that more speciesrich plant communities contained a greater diversity of plant pathogens and thus had strong negative impacts on invasive species. However, we found that S. canadensis and S. subulatum produced a similar amount of biomass when they were grown in the soils inoculated with the soil microbes from the native plant communities with different levels of species richness, and E. canadensis even produced more biomass in the soil inoculated with the soil microbes from the more diverse plant communities.…”
Section: Direct Effects Of Soil Microbes On the Growth Of Invasive Pl...mentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that the species richness of native plant communities can affect the diversity, abundance activity of soil pathogens increase with species richness in native plant communities, then soils from native plant communities with higher species richness should have a stronger negative effect on the growth of invasive plants. For instance, in a recent study, Zhang et al (2020) showed that more speciesrich plant communities contained a greater diversity of plant pathogens and thus had strong negative impacts on invasive species. However, we found that S. canadensis and S. subulatum produced a similar amount of biomass when they were grown in the soils inoculated with the soil microbes from the native plant communities with different levels of species richness, and E. canadensis even produced more biomass in the soil inoculated with the soil microbes from the more diverse plant communities.…”
Section: Direct Effects Of Soil Microbes On the Growth Of Invasive Pl...mentioning
confidence: 99%
“…Ostfeld and Keesing 2012;Schmidt and Ostfeld 2001;Zhang et al 2020). The other reason may be that the effect of soil microbes on invasive plants was the net effect of the interaction between pathogenic and mutualistic soil microbes(Reinhart and Callaway 2006).…”
mentioning
confidence: 99%
“…If the diversity, abundance and/or activity of soil pathogens increase with species richness in native plant communities, then soils from native plant communities with higher species richness should have a stronger negative effect on the growth of invasive plants. For instance, in a recent study, Zhang et al (2020) showed that more speciesrich plant communities contained a greater diversity of plant pathogens and thus had strong negative impacts on invasive species. However, we found that S. canadensis and S. subulatum produced a similar amount of biomass when they were grown in the soils inoculated with the soil microbes from the native plant communities with different levels of species richness, and E. canadensis even produced more biomass in the soil inoculated with the soil microbes from the more diverse plant communities.…”
Section: Effect Of Soil Microbes On the Community Invasion Resistancementioning
confidence: 99%
“…In invaded communities, alien species may be strongly negatively affected by some of the native soil pathogens because they have not co-evolved with those pathogens (Fries 2016;Zhang et al 2020). As an increase in native plant species richness may increase the diversity and abundance of native soil pathogens (Hudson et al 2006; Keesing et al 2006), more species-rich native plant communities will likely contain native soil pathogens that negatively affect the growth of exotic plants, thus increasing their resistance to exotic plant invasions.…”
mentioning
confidence: 99%
“…Invasional meltdown has been studied across a variety of ecosystems, with empirical evidence coming from terrestrial plant, vertebrate, and invertebrate communities (Relva et al 2010;Green et al 2011;Ackerman et al 2014;Collins et al 2020), as well as freshwater plants and vertebrates (Ricciardi 2001; Meza-Lopez and Siemann 2015; Crane et al 2020), and marine invertebrate communities (Grosholz 2005;Freeman et al 2016). At the same time, biotic resistance (decreased exotic establishment in more diverse communities) has been demonstrated in terrestrial (Levine et al 2004;Beaury et al 2020;Zhang et al 2020), freshwater (Fitzgerald et al 2016;Liew et al 2016), and marine (Stachowicz et al 1999;Stachowicz and Byrnes 2006;Kimbro et al 2013;Marra ni and Geller 2015) communities.…”
Section: Introductionmentioning
confidence: 99%